2015
DOI: 10.1021/acs.jpcb.5b01502
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxations of (Acetamide + Electrolyte) Deep Eutectic Solvents in the Frequency Window, 0.2 ≤ ν/GHz ≤ 50: Anion and Cation Dependence

Abstract: Dielectric relaxation (DR) measurements in the frequency range 0.2 ≤ ν/GHz ≤ 50 have been carried out for neat molten acetamide and six different (acetamide + electrolyte) deep eutectic solvents (DESs) for investigating ion effects on DR dynamics in these ionic DESs. Electrolytes used are lithium salts of bromide (LiBr), nitrate (LiNO3), and perchlorate (LiClO4); sodium salts of perchlorate (NaClO4) and thiocyante (NaSCN); and potassium thiocyanate (KSCN). With these electrolytes acetamide forms DESs approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 88 publications
9
62
1
Order By: Relevance
“…Similar relaxation processes were previously only detected in few other DESs, moreover in rather restricted temperature and/or frequency ranges only. 35,37,53 In principle, the ' spectra shown in the inset of Fig. 1 closely resemble those of conventional dipolar liquids under supercooling, 12,20,48,55 which could be expected when considering that 2/3 of the samples indeed consist of such a dipolar liquid.…”
Section: Methodssupporting
confidence: 57%
“…Similar relaxation processes were previously only detected in few other DESs, moreover in rather restricted temperature and/or frequency ranges only. 35,37,53 In principle, the ' spectra shown in the inset of Fig. 1 closely resemble those of conventional dipolar liquids under supercooling, 12,20,48,55 which could be expected when considering that 2/3 of the samples indeed consist of such a dipolar liquid.…”
Section: Methodssupporting
confidence: 57%
“…In such ac ase, the hydrodynamicd escriptioni se xpected to provide results that may either be inconsistent or bury the subtle ef-fects of environmental complexity. [76] In light of these discussions, the presentinapplicability of the hydrodynamics description in describing the solute rotationi nahydroxyl-functionalized IL perhaps indicatest he involvement of orientational jumpsa nd the role of hydrogen-bond formationi nt hat event.…”
Section: Time-resolveds Tudiesmentioning
confidence: 85%
“…[42] Details of the calculation procedure have been described in our earlier publications. [55] Recent theoreticali nvestigations by Biswas et al [76] have also demonstrated that the jumpd ynamics and hydrogen-bond fluctuations are closely related in highly viscous media such as IL. [32] The slip and stick boundary limits that were assigned with the help of SED hydrodynamic theory are shown in Figure 7w ith the experimentally measuredr eorientation times of C153 in the presentI Ls.…”
Section: Time-resolveds Tudiesmentioning
confidence: 98%
See 2 more Smart Citations